2021
DOI: 10.1055/s-0041-1735821
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of the Combination of MGMT Methylation and TERT Promoter Mutation in Glioblastoma

Abstract: Background The concept of combinational analysis between the methylation of O6-methylguanine-DNA methyltransferase (MGMT) and telomerase reverse transcriptase promoter (pTERT) mutation in glioblastoma (GBM) has been reported. The main study objective was to determine the prognosis of patients with GBM based on MGMT/pTERT classification, while the secondary objective was to estimate the temozolomide effect on the survival time of GBM with MGMT/pTERT classification. Methods A total of 50 GBM specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…When there are several time endpoints, a time-to-event analysis may better capture the natural course of CSDH and be more appropriate than binary logistic regression. 14,15 Risk factors related to the recurrence of CSDH following surgery have still been discussed and are uncertain from prior studies. As result, preoperative clopidogrel usage and the amount of saline irrigation were potentially associated with the recurrence of CSDH in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When there are several time endpoints, a time-to-event analysis may better capture the natural course of CSDH and be more appropriate than binary logistic regression. 14,15 Risk factors related to the recurrence of CSDH following surgery have still been discussed and are uncertain from prior studies. As result, preoperative clopidogrel usage and the amount of saline irrigation were potentially associated with the recurrence of CSDH in this study.…”
Section: Discussionmentioning
confidence: 99%
“…When there are several time endpoints, a time-to-event analysis may better capture the natural course of CSDH and be more appropriate than binary logistic regression. 14 15…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, patients with IDH wild-type and TERT promoter (pTERT) mutant gliomas in the new classification are also diagnosed with GBM. Studies on the status of pTERT and MGMT in GBM have also been reported (5), but there are few studies on pTERT mutations and MGMT methylation status in other types of ADG in the new classification.…”
Section: Introductionmentioning
confidence: 99%